Heterotopic pregnancy. Case report and literature review. - Malaver, José (2015)
The characteristics of a case of heterotopic pregnancy confirmed by laparotomy is described and the literature is reviewed. This was a woman of 31, who entered the hospital with abdominal pain and shock. Pelvic ultrasound showed uterus occupied by active seven weeks gestation, and a right adnexal mass in the interior oval image echolucent appreciated. Histopathology showed tubal pregnancy.